Improving Students' Science Literacy and Collaboration Skills Through Culturally Responsive Transformative Teaching Model with Podcasts and E-Assessment - Dhea Nur Magfiroh; Sri Yamtinah; Antuni Wiyarsi; Hayuni Retno Widarti; Ari Syahidul Shidiq; Dhea Nur Magfiroh; Sri Yamtinah; Antuni Wiyarsi; Hayuni Retno Widarti (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study was motivated by the low level of science literacy and collaboration skills among students. One effort to overcome this problem is to apply the Culturally Responsive Transformative Teaching (CRTT) model, which emphasizes active student involvement through the integration of cultural backgrounds and social interactions, supported by podcasts as a learning medium and e-assessment as a more effective evaluation tool. This study aims to analyze the effect of the CRTT model with podcasts and e-assessment on students' science literacy and collaboration skills. This study uses a quantitative approach with a quasi-experimental method and uses a pretest-posttest control group design. The sample consisted of 72 high school 11th grade students selected through cluster random sampling. Data were collected using science literacy tests and collaboration skill observations. Data analysis was performed using parametric statistical tests with hypothesis testing through MANOVA. The results of this study indicate a significant difference between students taught using the CRTT model assisted by podcasts and e-assessment and students not taught using this model and media. Applying the CRTT model with podcasts and e-assessment has been proven to improve students' science literacy and collaboration skills. The implications of this study indicate that the CRTT learning model, supported by digital media and e-assessment, can be an alternative strategy for teaching chemistry especially for reaction rate material.